Material de referencia piloto: Sal de biftalato de potasio, Código INM-030-1 lote 231228 - GINA ALEXANDRA TORRES LOPEZ; OLGA BRIGETTE SUAZA DIAZ; CRISTHIAN PAREDES CARDONA; JULIO CESAR TORRIJOS LAVADO; Paredes Cardona, Cristhian; Suaza Diaz, Olga Brigette (Instituto Nacional de Metrología - INM, 2023)
Material de referencia piloto: Sal de biftalato de potasio, Código INM-030-1 lote 231228